REVENGE AS MIMETIC DESIRE IN JUAN RULFO’S TELL THEM NOT TO KILL ME! - Sarmi, Ni Nyoman; Suyaji, Fransisca Irnidianis Magdalena; Pasopati, Rommel Utungga (Department of English Literature, Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
In some stories, the development of the characters is motivated by desire. While modern ideas define desire as autonomous, René Girard analyzes desire as imitation from others. “Tell Them Not to Kill Me!” is Juan Rulfo’s short story that tells a story of a fugitive of murder that had to face the death penalty. He fled for thirty years thinking that everyone has forgotten his case, but then he was caught by the Colonel who was the son of the one he murdered. The death penalty was a revenge from a son to his father’s murderer. This paper then focuses on exploring the ways revenge is seen as a mimetic desire in Juan Rulfo’s “Tell Them Not to Kill Me!”. Through the perspective of Girard’s theory of desire, this paper shows that revenge becomes a direct reflection of murder that has been done before. The desire to murder is not spontaneous but determined by the former action. The desire to murder that is expressed by Colonel enables him to punish those who commit crime. ‘The eye for an eye’ is a statement that will not happen if one's own eye is not taken beforehand. Through Girard’s perspective, Rulfo’s story provides evidence that the Colonel’s desire to revenge is mimetic of murder which results in the death penalty of the murderer. In conclusion, the Colonel’s desire is not perceived as positive or negative but a mimesis to the previous other’s deeds.